FAKTOR-FAKTOR RISIKO STROKE PADA PENYAKIT GINJAL KRONIK STADIUM V YANG MENJALANI HEMODIALISIS - Ariani, Susanti Dwi; Tugasworo, Dodik; Widiastuti Samekto, Maria Imakulata (Majalah Kedokteran Neurosains Perhimpunan Dokter Spesialis Saraf Indonesia, 2018)
RISK FACTORS OF STROKE IN STAGE V CHRONIC KIDNEY DISEASE WHO UNDERWENT HEMODIALYSISABSTRACTIntroduction: Chronic kidney disease (CKD) and end-stage renal disease are associated with a significantly in- creased risk of stroke. Incidence and mortality of stroke in CKD patients is higher rather than among the general popula- tion. Stroke in hemodialysis patients is also associated with high mortality.Aims: To analyze risk factors that have a relationship with the occurrence of stroke in patients with stage V CKD who underwent hemodialysis in Dr. Kariadi Hospital, Semarang.Method: A case control with retrospective cohort study of patients diagnosed with stage V CKD undergoing hemo- dialysis in Dr. Kariadi Hospital, Semarang, from March 2016 to August 2017. Subject was divided into case group, who experienced stroke, and control group, who did not experience stroke. Bivariate analysis was performed with Chi-square test, multivariate analysis with logistic regression test and rasio Odds.Results: There were 140 subjects with stage V CKD, 70 subjects in each groups. In case group, 85.7% experienced ischemic stroke while the rest hemorrhagic stroke. The duration of hemodialysis was related to the incidence of stroke. In multivariate analysis, patients with diabetes mellitus were more likely to have a stroke by 0.14 times compared to patients who did not have diabetes mellitus, and patients who underwent hemodialysis >12 months, were more likely to have a stroke 4.05 times greater than patients who underwent hemodialysis <12 months.Discussion: There is a relationship between diabetes mellitus and duration of hemodialysis with the occurrence of ischemic stroke, in stage V CKD patients who underwent hemodialysis.Keywords: Chronic kidney disease, hemodialysis, strokeABSTRAKPendahuluan: Penyakit ginjal kronik (PGK) dan penyakit ginjal stadium akhir terkait dengan peningkatan risiko yang signifikan dari stroke. Insiden dan mortalitas stroke pada pasien PGK lebih tinggi dibandingkan populasi umum. Stroke pada pasien dialisis juga dihubungkan dengan mortalitas yang tinggi.Tujuan: Untuk menganalisis faktor-faktor risiko yang memengaruhi terjadinya stroke pada pasien dengan PGK stadium V yang menjalani hemodialisis (HD) di RSUP Dr. Kariadi, Semarang.Metode: Penelitian kasus kontrol dengan pendekatan kohort retrospektif terhadap pasien penyakit ginjal kronik stadium V yang menjalani HD di RSUP Dr. Kariadi, Semarang dari bulan Maret 2016 hingga Agustus 2017. Subjek dibagi ke dalam kelompok kasus, yaitu yang mengalami stroke dan kelompok kontrol yang tidak mengalami stroke. Dilakukan analisis bivariat dengan uji Chi-square dan analisis multivariat dengan uji regresi logistik serta rasio Odds.Hasil: Didapatkan 140 subjek dengan PGK stadium V yang masing-masing kelompok terdiri dari 70 orang. Pada kelompok kasus, sebanyak 85,7% adalah stroke iskemik dan sisanya stroke hemoragik. Lama HD berhubungan dengan kejadian stroke. Pada uji multivariat, subjek yang menderita diabetes melitus (DM) berisiko mengalami stroke sebesar 0,14 kali dibandingkan yang tidak DM dan subjek yang menjalani HD >12 bulan berisiko mengalami stroke 4,05 kali lebih besar dibandingkan yang menjalani HD <12 bulan.Diskusi: Terdapat pengaruh faktor risiko DM dan lama hemodialisis terhadap kejadian stroke iskemik pada pasien PGK stadium V yang menjalani HD.Kata kunci: Hemodialisis, penyakit ginjal kronik, stroke